STRUCTURAL CHARACTERISTICS OF FOREST STATE IIIA3 BETWEEN TWO ALTITUDE LEVELS IN CORE ZONE IN XUAN NHA NATURE RESERVE, VAN HO DISTRICT, SON LA PROVINCE - Danh Toan, Cao; Thi Thu Hien, Cao (Journal of Forestry Science and Technology, 2019)
This study was conducted to understand altitudinal changes in stand structure and tree species diversity in evergreen broadleaf forest in core zone in Xuan Nha Nature Reserve. Six plots (20 m x 40 m), distributing between < 1,000 and > 1,000 m above sea level were used for stem census. All stems with diameter at breast height (DBH) ≥ 6 cm were identified to species and measured for DBH and height. Results indicated elevation zone of > 1,000 m above sea level had higher mean diameter, mean height, and basal area than those of < 1,000 m. The stem density and tree species diversity in > 1,000 m were slightly lower than that in < 1,000 m. There was virtually no difference in the frequency distributions of the DBH across the two altitudinal zones. Those distributions were all skewed to the left of the graph, with the total number of stems dramatically declining with the ascending DBH classes. In regard of relationship between tree height and diameter, the logarithmic function was chosen to describe this relationship. The highest number of regeneration trees focused on the first height class for both altitude above 1,000 m and below 1,000 m. Generally, most of regeneration trees in two altitude levels had good quality, and originated in seeds.